Impartiality, statistical tit-for-tats and the construction of balance: UK television news reporting of the 2016 EU referendum campaign. (June 2017) - Cushion, Stephen; Lewis, Justin
There has been greater news industry recognition in recent years that impartiality should not be translated into simply balancing the competing sides of a debate or issue. The binary nature of a referendum campaign represents a unique moment to consider whether broadcasters have put this into practice beyond routine political reporting. This study examines how impartiality was editorially interpreted in television news coverage during the United Kingdom's 2016 European Union referendum. We carried out a systematic content analysis of the United Kingdom's main evening bulletins over the 10-week campaign, examining the issues and sources shaping coverage, as well as all the statistical claims made by campaign actors. Our aim was to critically examine how notions of impartiality were constructed and interpreted, exploring any operational limits and political consequences. Overall, we found that news bulletins maintained a fairly strict adherence to a central binary balance between issues and actors during the campaign. But this binary was politically inflected, with a significant imbalance in party political perspectives, presenting us with a right-wing rather than a left-wing case for European Union membership. We also found that independent expert analysis and testimony was sucked into the partisan binary between leave and remain campaigners, while journalists were reluctant to challenge or contextualise claims and counter-claims. Journalists were, in this sense, constrained by the operational definition of impartiality adopted by broadcasters. We argue for a more evidence-driven approach to impartiality, where journalists independently explore the veracity of campaign claims and have the editorial freedom to challenge them. We also suggest that the reliance on claims and counter-claims by leading Conservative politicians did little to advance public understanding of the European Union, and helped perpetuate a series of long-standing negative associations the British media have been reporting for many decades.